Eukaryotic transcription initiation machinery visualized at molecular level. Issue 5 (19th October 2016) - Han, Yan; He, Yuan
ABSTRACT: The structures of RNA Polymerase (Pol) II pre-initiation complexes (PIC) have recently been determined at near-atomic resolution, elucidating unprecedented mechanistic details of promoter opening during transcription initiation. The key structural features of promoter opening are summarized here. Structural knowledge of Pol I and III PIC is also briefly discussed.